A review on energy scenario and sustainable energy in Iran - Mohammadnejad, M.; Ghazvini, M.; Mahlia, T.M.I.; Andriyana, A. (Elsevier, 2015)
Energy has a key role in social-economic development of countries. Fossil fuels which have a large contribution in energy consumption in the world, are depleting and it seems necessary to find alternative energy sources. Today, energy consumption in Iran is increasing due to population growth and economic development. This study presents an overview of the energy resources, supply and demand as the current energy scenario in Iran. Also, this study discusses other kinds of energy especially renewable energy such as wind, solar, biomass and geothermal as the alternative for energy supply in this country. It is found that, since the country has many windy areas and at least 2800 sunshine hours per year, it has high potential for utilizing wind and solar energy. Therefore, Iran must try to optimize energy consumption especially in the residential sector and increase the contribution of renewable energy in energy supply to make the energy mix secure and environmentally sustainable. (C) 2011 Elsevier Ltd. All rights reserved.